Perbandingan Efektivitas Media Kotoran Sapi, Kambing, Ayam, dan Puyuh pada Produktivitas Maggot BSF (Hermetia illucens) sebagai Sumber Protein Alternatif - Amelia, Tria; Sulaiman, Abrani; Biyatmoko, Danang (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2025)
This study aimed to analyze the effect of different livestock manure media (cow, goat, laying hen,and quail) on the growth rate and productivity of Hermetia illucens (BSF) maggots as analternative protein source for livestock. A Completely Randomized Design (CRD) with fourtreatments and five replications was employed, involving measurements of maggot weight,length, and biomass over 21 days. Results showed that laying hen manure yielded the highestweight growth rate (3.07%/day; 47.32 mg/individual) and biomass productivity (302.2 g),attributed to its highest crude protein content (19.74%). Conversely, goat manure (4.6% protein)resulted in the lowest growth rate (0.75%/day; 12.16 mg/individual). Optimal maggotperformance in laying hen manure was supported by adequate nutrition and environmentalconditions (temperature 28.5–30°C, humidity 80–94%). This research demonstrates the potentialof livestock manure as a sustainable medium for maggot cultivation, reducing feed costs andpromoting circular economies through organic waste conversion